2012
DOI: 10.1126/science.1220801
|View full text |Cite|
|
Sign up to set email alerts
|

Observation of 239 Pu Nuclear Magnetic Resonance

Abstract: In principle, the spin-½ plutonium-239 ((239)Pu) nucleus should be active in nuclear magnetic resonance spectroscopy. However, its signal has eluded detection for the past 50 years. Here, we report observation of a (239)Pu resonance from a solid sample of plutonium dioxide (PuO(2)) subjected to a wide scan of external magnetic field values (3 to 8 tesla) at a temperature of 4 kelvin. By mapping the external field dependence of the measured resonance frequency, we determined the nuclear gyromagnetic ratio (239)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
60
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 17 publications
4
60
2
Order By: Relevance
“…26 A recent Pu-NMR study confirmed the nonmagnetic character of the ground state of PuO 2 . 18 In AmO 2 a clear antiferromagnetic-looking phase transition is observed at 8.5 K, 15 however, no magnetic moment has been observed in Mössbauer nor in neutron scattering measurements. 16,17 The fingerprint of this dioxide is similar to the one obtained in earlier studies of NpO 2 , and hence, an AF-MPO state is expected in AmO 2 .…”
Section: Splitting Of One Electron Orbital (Schematic)mentioning
confidence: 99%
See 1 more Smart Citation
“…26 A recent Pu-NMR study confirmed the nonmagnetic character of the ground state of PuO 2 . 18 In AmO 2 a clear antiferromagnetic-looking phase transition is observed at 8.5 K, 15 however, no magnetic moment has been observed in Mössbauer nor in neutron scattering measurements. 16,17 The fingerprint of this dioxide is similar to the one obtained in earlier studies of NpO 2 , and hence, an AF-MPO state is expected in AmO 2 .…”
Section: Splitting Of One Electron Orbital (Schematic)mentioning
confidence: 99%
“…8,9 AmO 2 undergoes a conspicuous phase transition at around 8.5 K. 15 While a peak structure in the magnetic susceptibility was found, 15 neutron-diffraction measurements could not detect antiferromagnetic order in agreement with the Mössbauer measurement. 16,17 PuO 2 is a simple nonmagnetic insulator, 18 whereas CmO 2 has an unexpected paramagnetic moment. 19 Surprisingly, each of these actinide dioxides is an insulator, in spite of the very different emerging orders and physical properties.…”
Section: Introductionmentioning
confidence: 99%
“…For the actinide series two nuclei are of practical use, namely 235 U [3,4] (I¼ 7/2) and 239 Pu [5] (I ¼1/2), but unfortunately only at very low temperatures because the very fast spin-lattice relaxation rate makes the signal vanish quickly with increasing temperature (e.g. no signal was detected above 14 K for 235 U).…”
Section: Introductionmentioning
confidence: 99%
“…no signal was detected above 14 K for 235 U). Few installations exist around the world where NMR studies can be carried out on nuclear materials [5][6][7][8][9][10]. Here, we focus on a model compound and examine its magnetic properties by magnetization, susceptibility, and low-temperature NMR measurements.…”
Section: Introductionmentioning
confidence: 99%
“…1 For instance, multiple DFT calculations have indicated an AFM ground-state, which contrasts with the DM state established by experimental methods. [107][108][109][110] The mechanisms behind such an intriguing electronic states are not yet fully understood and the crystal and magnetic structures of NpO2 have still not been resolved.…”
mentioning
confidence: 99%